Molecular characterization of Malaysian methicillin-resistant Staphylococcus aureus - Lim, Tien Tze (Curtin University, 2007)
Seventy-four methicillin-resistant Staphylococcus aureus (MRSA) from two Malaysian hospitals were characterised by both phenotypic and genotypic techniques. These isolates were collected over an 18 year time period in the years, 1982, 1989, 1994 and 2000. All of the Malaysian MRSA isolates were found to be multiresistant and resistant to at least five different antimicrobial agents. Over 30% of them were non-typable by the International Basic Set of bacteriophages. The majority of the typable isolates were susceptible to the group III phages, especially phage 85. The majority of the isolates carried one to six plasmids. Only two isolates were plasmid free. The plasmid profiles of these isolates, other than the 1982 isolates, were very similar to each other. Contour-clamped homogeneous electric field (CHEF) gel electrophoresis was used to examine the genetic relatedness of the isolates. Twenty-six CHEF patterns were found among the isolates. These CHEF patterns were closely related to each other. The predominant CHEF pattern A was found in the 1982, 1989 and 1994 isolates. The CHEF patterns of the year 2000 isolates were different to CHEF pattern A, but still closely related. All of the isolates were found to carry the Allotype III SCCmec and have coagulase-gene type 24. Multilocus sequence typing was preformed on the isolates with CHEF pattern A collected in different years. These isolates were found to have either sequence type 239 (ST239), or its single locus variant. The predominant Malaysian clone belongs to the pandemic clone ST239-MRSA-III that is pandemic in Asian countries. (Enright, 2003, Ko et al., 2005).A 1.5 kb cryptic plasmid found in Malaysian isolates was indistinguishable from a cryptic plasmid found in an Australian isolate. A 3.0 kb cryptic plasmid found in Malaysian isolates was undistinguishable from a 3.0 kb plasmid found in Singaporean isolates. Class II multiresistance plasmids of 28, 30.5 and 35 kb were commonly found together in many Malaysian MRSA isolates. Both the 28 and 30.5 kb plasmids encode resistance to the heavy-metals and nucleic acid-binding (NAB) compounds. The 35 kb plasmid carries heavy-metal and NAB resistance but also encodes β-lactamase. Structurally these three plasmids are almost identical and probably have the same origin. The differences observed between these plasmids is probably due to excision or partial deletion of the β-lactamase transposon of the original plasmid. The 28 kb plasmid is identical to the 28 kb plasmid of Singaporean and some Australian isolates. A 20 kb plasmid in Indonesian isolates was found to be closely related to these three plasmids. A conjugative plasmid, pWBG707, conferring trimethoprim-resistance was found in Malaysian isolates. It did not carry either of the two staphylococcal trimethoprim-resistance genes, dfrA and dfrD. (Lyon and Skurray, 1987, Dale et al., 1995b) It either encodes a novel resistance gene or the recently discovered dfrG gene. (Sekiguchi et al., 2005) pWBG707 was also found to mobilise a small 3.0 kb kanamycin-resistance plasmid during conjugation.The mecR1 and mecI genes regulating the transcription of the methicillin-resistance gene, mecA, were also examined in the isolates. The Malaysian isolate, WBG7422, with the predominant CHEF pattern A has a nonsense mutation in its mecI gene that disables it. However, its mecR1 gene is intact. The eastern Australia MRSA (EA MRSA), WBG525, has a CHEF pattern that is closely related to the Malaysian predominant CHEF pattern A and its mecI gene has a mutation identical to the Malaysian isolate. Unlike the Malaysian isolate however, its mecR1 gene has a 166 bp deletion. Both WBG7422 and WBG525 express Class III heterogeneous methicillin resistance. However, WBG525 has more highly resistant cell in its population than WBG7422. The loss of aminoglycoside resistance, together with c. 114 kb of chromosomal DNA, was observed in some Malaysian isolates. The deleted segment was found to carry the aacA-aphD gene that encodes a bifunctional aminoglycoside-modifying enzyme conferring resistance to many of the aminoglycosides. The Malaysian isolates were compared with MRSA from different countries. These MRSA included 18 epidemic MRSA (EMRSA) from the United Kingdom, 15 Australian nosocomial MRSA, five classical MRSA, 22 community-acquired MRSA (CMRSA) from Australia and New Zealand and 46 nosocomial MRSAs from eight Asian-Pacific countries and South Africa. These Asian-Pacific countries were Australia, PR China, Hong Kong, Indonesia, Japan, Philippines, Singapore and Taiwan.The CHEF patterns of most of the Asian-Pacific and South African isolates were closely related to the Malaysian isolates. Isolates from Singapore, Indonesia and Philippines were found to have an identical CHEF pattern to the Malaysian CHEF patterns A5. The Asian-Pacific and South African isolates, including the Malaysian isolates, were found to be closely related to EMRSA-1, -4 and -7. These EMRSA belong to the ST239-MRSA-III clone and are coagulase-gene type 24. The isolates from Japan were the only Asian-Pacific isolates not related to the other Asian-Pacific isolates and EMRSAs. EMRSA-1 and EA MRSA have the same 166 bp deletion in their mecR1 gene. Both of these strains have closely related CHEF patterns, the same sequence type, coagulase-gene type and SCCmec. These results indicate that these two strains belongs to the same clone and confirms the international spread of this clone in the early 1980s. However, the Malaysian isolates have CHEF patterns that are more closely related to EMRSA-4 than to EMRSA-1. Similar to the Malaysian isolates EMRSA-4 has an intact mecR1 gene. The CMRSA isolates were not related to any of the nosocomial MRSA. They also have very diverse genetic backgrounds but carry less diverse SCCmec allotypes. Most of the CMRSA carry either Allotype IV or V SCCmec These results show that the spread of Malaysian MRSA is due to a single clonal expansion. Infection control measures would have to have been more efficient if this clone was to have been contained. The Malaysian epidemic clone is the Asian pandemic clone, ST239-MRSA-III. The Malaysian isolates and EMRSA-4 probably share the same ancestor.The presence of the same MRSA strain in Malaysian hospitals and in the hospitals of neighbouring countries indicates that the inter-hospital spread of an epidemic MRSA has occurred. This observation also suggests that the infection control measures in Malaysian hospitals have not been totally effective. The ineffectiveness of infection control has left Malaysian hospitals vulnerable to the future importation of new pandemic clones and/or highly virulent or resistant clones.